ANALYTICAL STUDY RELATING TO GAIN MUSCLE STRENGTH OF LOWER LIMB FOR MEN AND WOMEN PRACTITIONERS BODY PUMP (Fiep Bulletin - online, 2011)
The aim of this study is to compare the effects of training BODY PUMP, the levels of muscular endurance (RML) of the lower limbs of adult men and women non-athletes. The sample comprised 20 individuals divided into two groups: 10 men (n = 10), with a mean age of 24.5, and women (n = 10), with a mean age of 26.5. Data were drawn from the songs 2 (half squat) and 7 (unilateral squat or sink), the classes of the mix BODY PUMP 69, for lower limbs, checking the initial charge of training. After obtaining these data, we performed the statistical descriptive study to define the profile of each group. We used the statistical test t-student, because through it is possible to compare two independent groups, searching for differences in central tendency, variability, kurtosis or any other. The results indicate that there are significant differences between the levels of gain muscular endurance (RML) in the lower limbs when compared to the beginning of training. However, we can conclude that the BODY PUMP is an excellent form of training of muscular endurance (RML), he obtained statistically significant results compared to the beginning of training, helping to overturn the myth that only the weights used to the training of muscular endurance (RML).The results also encourage those who for various reasons cannot or do not like training in weight rooms, thus providing a new option of training in gyms, clubs, spa or similar places.
Keywords: Body Pump; Muscular endurance; and Legs